2015
DOI: 10.1016/j.algal.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of centrate from wastewater treatment for the outdoor production of Nannochloropsis gaditana biomass at pilot-scale

Abstract: In this work, the outdoor pilot-scale production of marine microalga Nannochloropsis gaditana using centrate from the anaerobic digestion of municipal wastewater was evaluated. For this, outdoor semi-continuous cultures were performed in both tubular and raceway reactors mixing seawater with different centrate percentages (15%, 20% and 30%) as culture medium. It was demonstrated that N. gaditana can be produced using centrate as the only nutrient source but at percentages below 30%. At this level inhibition wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 35 publications
5
49
0
2
Order By: Relevance
“…This result is in agreement with a previous report claiming strains related to these two species were the most efficient in growing in wastewater-derived substrates [39]. Only in the case of N. gaditana did it appear that any digestates could sustain algal growth, while previous works reported the possibility of using anaerobically digested municipal wastewater for N. gaditana [40] or Nannochloropsis salina [41,42] cultivation. The low salinity of the different digestates, especially upon dilution, is likely the main reason for the absence of growth of N. gaditana , since in a previous report it was found that the anaerobic digestates investigated were diluted with artificial salt water.…”
Section: Discussionsupporting
confidence: 92%
“…This result is in agreement with a previous report claiming strains related to these two species were the most efficient in growing in wastewater-derived substrates [39]. Only in the case of N. gaditana did it appear that any digestates could sustain algal growth, while previous works reported the possibility of using anaerobically digested municipal wastewater for N. gaditana [40] or Nannochloropsis salina [41,42] cultivation. The low salinity of the different digestates, especially upon dilution, is likely the main reason for the absence of growth of N. gaditana , since in a previous report it was found that the anaerobic digestates investigated were diluted with artificial salt water.…”
Section: Discussionsupporting
confidence: 92%
“…18 Seawater microalgae species have also been used to treat WW despite their salinity requirements. 19 Growth of microalgae in WW has been studied under various physiochemical conditions such as light, temperature, pH, CO 2 concentration, and nutrients, but the use of WW for the production of algal-based biofuel has not been explored extensively yet. 20,21 Thus, the scope of this study was to identify an algal strain that efficiently remediates municipal WW and can be used for biofuel production.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…As shown in Table , the amount of stripped N was lower with CO 2 supply and this is related to the better microalgae growth. The quantification of stripped N is an important aspect of microalgae‐based treatment to understand the N removal mechanism, as already demonstrated by Ledda et al …”
Section: Resultsmentioning
confidence: 90%